2022
DOI: 10.3389/fmed.2022.875242
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Perception of Artificial Intelligence Usability in Eye Care (APPRAISE) for Ophthalmologists: A Multinational Perspective

Abstract: BackgroundMany artificial intelligence (AI) studies have focused on development of AI models, novel techniques, and reporting guidelines. However, little is understood about clinicians' perspectives of AI applications in medical fields including ophthalmology, particularly in light of recent regulatory guidelines. The aim for this study was to evaluate the perspectives of ophthalmologists regarding AI in 4 major eye conditions: diabetic retinopathy (DR), glaucoma, age-related macular degeneration (AMD) and cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Another area for progress is the integration of AI with teleglaucoma modalities [43,44]. In a survey of 1176 ophthalmologists from 70 countries, 70.7% reported that they would be willing to integrate AI for glaucoma screening [45 ▪ ]. Certainly, this confidence can be justified by recent advancements.…”
Section: Discussionmentioning
confidence: 99%
“…Another area for progress is the integration of AI with teleglaucoma modalities [43,44]. In a survey of 1176 ophthalmologists from 70 countries, 70.7% reported that they would be willing to integrate AI for glaucoma screening [45 ▪ ]. Certainly, this confidence can be justified by recent advancements.…”
Section: Discussionmentioning
confidence: 99%
“…More work is also needed to explore XAI methods in AI applications beyond medical image analysis [53 ▪▪ ], including unstructured data in large language models. In assessing the usefulness of XAI explanations, more emphasis on end-users perspectives, including clinicians, patients, and policymakers, should be explored to guide the improvement of XAI methods [12 ▪▪ ,17 ▪▪ ,54 ▪ ]. Finally, in addition to enhancing the transparency of AI models, concerted effort is needed along all stages of model development from data collection to deployment, to address all pillars in developing trustworthy AI [55,56 ▪▪ ].…”
Section: Discussionmentioning
confidence: 99%
“…Since ophthalmologists are receptive to adopting AI as an assistive tool for glaucoma,53 as soon as results of predictive models using AI are available to general ophthalmologists, modern clinical decision-support systems may become important tools to improve decision-making in the teleglaucoma setting 54. However, application in clinical practice still requires careful validation with transparent reporting that follows all AI guidelines 55–58.…”
Section: Teleglaucomamentioning
confidence: 99%